Biosynthesis of Fatty Alcohols in Engineered Microbial Cell Factories: Advances and Limitations - Krishnan, Anagha; McNeil, Bonnie A.; Stuart, David T. (Frontiers in Bioengineering and Biotechnology, 2020)
Concerns about climate change and environmental destruction have led to interest in technologies that can replace fossil fuels and petrochemicals with compounds derived from sustainable sources that have lower environmental impact. Fatty alcohols produced by chemical synthesis from ethylene or by chemical conversion of plant oils have a large range of industrial applications. These chemicals can be synthesized through biological routes but their free forms are produced in trace amounts naturally. This review focuses on how genetic engineering of endogenous fatty acid metabolism and heterologous expression of fatty alcohol producing enzymes have come together resulting in the current state of the field for production of fatty alcohols by microbial cell factories. We provide an overview of endogenous fatty acid synthesis, enzymatic methods of conversion to fatty alcohols and review the research to date on microbial fatty alcohol production. The primary focus is on work performed in the model microorganisms, Escherichia coli and Saccharomyces cerevisiae but advances made with cyanobacteria and oleaginous yeasts are also considered. The limitations to production of fatty alcohols by microbial cell factories are detailed along with consideration to potential research directions that may aid in achieving viable commercial scale production of fatty alcohols from renewable feedstock.